2019
DOI: 10.1038/s41577-019-0124-9
|View full text |Cite
|
Sign up to set email alerts
|

Immunometabolism at the interface between macrophages and pathogens

Abstract: It is generally regarded that the progression of an infection within host macrophages is the consequence of a failed immune response. However, recent appreciation of macrophage heterogeneity, with respect to both development and metabolism, indicates that the reality is more complex. Different lineages of tissue-resident macrophages respond divergently to microbial, environmental and immunological stimuli. The emerging picture that the developmental origin of macrophages determines their responses to immune st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
292
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 343 publications
(320 citation statements)
references
References 159 publications
3
292
0
Order By: Relevance
“…High glycolytic rate pro‐inflammatory macrophages clear the intracellular bacteria via metabolites. In contrast, anti‐inflammatory macrophages permit the persistence of bacteria, which leads to a non‐effective antibiotic treatment . Thus it is desirable to develop novel drugs targeting the macrophage metabolic phenotype to control bacterial infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…High glycolytic rate pro‐inflammatory macrophages clear the intracellular bacteria via metabolites. In contrast, anti‐inflammatory macrophages permit the persistence of bacteria, which leads to a non‐effective antibiotic treatment . Thus it is desirable to develop novel drugs targeting the macrophage metabolic phenotype to control bacterial infection.…”
mentioning
confidence: 99%
“…Our phenotyping data suggested that dPGS treatment enhances the expression of pro‐inflammatory signature genes as well as cytokines, here we found a negative regulation of dPGS on mitochondrial respiration of M2 macrophages. Several studies already stated that metabolic reprogramming seems to be a key feature to trigger final macrophage function . Regarding the correlation of metabolic pathways and the effective macrophage phenotype in bacterial infection, the immunomodulation of dPGS might pave the way to develop novel therapeutic strategies.…”
mentioning
confidence: 99%
“…Finally, these data need to be integrated with our current understanding of human disease. This figure is modified from Russell et al ()…”
Section: Host Cell Metabolismmentioning
confidence: 99%
“…Indeed, MACs are extremely plastic in disease and much research has focused around TAMs and their bidirectional communication with the environment. For example, tumors attract MACs which are recruited by a hypoxic environment and CCL2 expression . Once recruited MACs play an immunosuppressive role promoting tumor survival while also being metabolically reprogrammed to use glycolysis, which is favourable in the tumor's environment .…”
Section: Introductionmentioning
confidence: 99%
“… For example, tumors attract MACs which are recruited by a hypoxic environment and CCL2 expression . Once recruited MACs play an immunosuppressive role promoting tumor survival while also being metabolically reprogrammed to use glycolysis, which is favourable in the tumor's environment . Interestingly, human HFs share many features with tumors such as rapid proliferation and a preference for glycolytic metabolism.…”
Section: Introductionmentioning
confidence: 99%